CFD-based numerical study on drag reduction of ventilated supercavities combined with gas layer of the surface vehicle with struts. (15th October 2022) - An, Hai; Pan, Haozhe; Yang, Po
Abstract: Drag reduction by artificial ventilation is a promising engineering method for improving ship performance. In the present study, a novel drag reduction approach of ventilated supercavities combined with gas layer is proposed for high speed surface vehicles with struts. Based on RANS equation, the SST turbulence model and the VOF multiphase flow model are used to numerically simulate the drag reduction scheme of artificially ventilated supercavities combined with gas layer of the surface vehicle with struts. The effect of the strut shape on the entrainment gas from the ventilated supercavities of the submerged body and the effect of the layout of auxiliary air vents on the coating efficiency of the bubble flow on the surface of submerged body are studied. And the skin friction coefficients of the vehicle under various auxiliary ventilation schemes are compared. The numerical results show that the shape of the strut and the position of the air vents relative to the strut on the submerged body have great influence on the skin friction resistance of the vehicle. Finally, the feasibility of the proposed scheme is verified by the model experiment. Highlights: The drag reduction approach of ventilated supercavities combined with air layer is an efficient drag reduction method for high speed surface vehicles with struts. Different strut shapes have different effects on gas entrainment from supercavities and the formation of bubble flow on the surface of submerged body. The leading edge air vents can improve drag reduction efficiency in the middle section of the submerged body. The trailing edge air vents can reduce the wetting area of the tail of the submerged body.